(untitled) (Afaq Lughawiyyah, 2024)
Stylistics is a link between linguistics and critical studies, as it starts with the literary text with the help of linguistic studies concerned with the structure of language and works to clarify linguistic issues in the literary text and determine their roles in clarifying the contents and linking them to the general content of literary discourse. This study of the poem "Be a balm for the poet Elia Abu Madi" came to highlight the most important stylistic characteristics that are unique to the poem, by revealing the most important phonetic elements in the poem and determining its semantic functions, and moving to the structures and images to reveal the implicit connotations of poetic discourse and its relationship to the content of the poem, as well as talking about the semantic fields that the poet employed in the text prominently, leading to the most important methods that the poet relied on in transferring meanings and connotations in the poem, with a focus on the significance of the counterpoint and the different graphic images of analogy, metaphor and metaphor. The research concluded a set of results, the most important of which are: that the poet adopted a simple style and clear language in highlighting his ideas, which in turn contributed to the statement of the idea clearly to the recipient, and was based in his poem on news sentences, achieving through them the purpose of wisdom in which a person needs the style of news, and the words indicative of movement are the most common in the poem that are in line with the purpose of the poem, and the poet has relied on images in abundance, which earned the poem life, spirit and human dimension felt by the reader during the transition between their meanings.